2020
DOI: 10.1002/rcm.8694
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characterization of small‐molecule inhibitors of monoamine oxidase B synthesized from the Acanthopanax senticosus root with affinity ultrafiltration mass spectrometry

Abstract: Rationale Discovering and identifying new small‐molecule inhibitors of monoamine oxidase B (MAO‐B) could provide the potential to treat many neurodegenerative diseases. Methods We employed affinity ultrafiltration liquid chromatography/tandem mass spectrometry (AUF‐LC/MSn) to identify and characterize small‐molecule inhibitors of MAO‐B from a 30% ethanolic extract of Acanthopanax senticosus root (ASR). In vitro tests were performed in stimulated BV2 microglia to evaluate the anti‐inflammatory effects of the AS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…is is consistent with the findings that the root of A. senticosus could potentially be used in the management of neurodegenerative diseases [29].…”
Section: Effects Of Differentsupporting
confidence: 92%
“…is is consistent with the findings that the root of A. senticosus could potentially be used in the management of neurodegenerative diseases [29].…”
Section: Effects Of Differentsupporting
confidence: 92%
“…For quinic acid, one previous study described the ability of this molecule to protect rats from aluminum chloride-induced dementia and suggested non-selective inhibition of MAO as a potential mechanism [ 38 ]. The selectivity of caffeoylquinic acid derivatives is unclear: two previous articles [ 37 , 39 ] provide evidence for selective activity against MAO-B, whereas another [ 40 ] also showed an effect against MAO-A.…”
Section: Discussionmentioning
confidence: 99%
“…Pure IF at 1 µM and 10 µM concentrations also showed remarkable effects on the lengths of axons and dendrites following a 4-day treatment [137,138]. Also, the monoamine oxidase B as the enzyme degeneration of nerve cells, involved in some neurological diseases including Alzheimer's disease was inhibited by pure IF, isolated from Acanthopanax senticosus, with a binding degree of 7.41% that had been determined by UPLC/MS/MS [30]. Considering these neuroprotective effects of IF, conducting more extensive studies on other aspects of this effect and involved pharmacological mechanisms could be helpful in introducing IF as a new drug molecule in the treatment of neurological diseases.…”
Section: Neuroprotective Effectsmentioning
confidence: 92%
“…Besides, the appearance of pieces at 194,166, 151(166-CH 3 ), and 123 m / z have been related to fracturing the C-O groups [ 38 , 70 , 100 ]. Also, another study reported that the IF showed a fragment at 163 m / z in MS/MS spectrum [ 30 ] ( Figure 3 ).…”
Section: Isofraxidinmentioning
confidence: 99%
See 1 more Smart Citation